CONTEXTUAL APPROACH IN MATHEMATICS LEARNING FOR ELEMENTARY SCHOOL CHILDREN - Sainab; Herna (CV. Fahr Publishing, 2025)
This study aims to investigate the implementation of a contextual teaching and learning (CTL) approach in elementary mathematics education by integrating real-life contexts, multimedia, and teacher scaffolding to enhance students’ conceptual understanding, reasoning, and communication skills. Employing a literature review method, the research systematically analyzes findings from peer-reviewed journals published within the last five years, focusing on empirical studies related to contextual-based mathematics instruction. The review reveals that CTL significantly improves student engagement, motivation, and problem-solving abilities when mathematical tasks are meaningfully connected to everyday life. Furthermore, the study identifies critical implementation variables—such as teacher readiness, instructional media, classroom size, and access to technology—that moderate the effectiveness of contextual strategies. The novelty of this research lies in its synthesis of CTL, multimedia, and differentiated instruction, offering a scalable instructional model tailored to varied learner needs and classroom contexts. It also highlights the role of teacher facilitation and digital tools as key enablers in delivering impactful contextual learning experiences. The study concludes that contextualized mathematics instruction, when designed and implemented thoughtfully, holds strong potential to make mathematics more meaningful, inclusive, and sustainable for elementary students. These findings offer valuable insights for educators, policymakers, and curriculum developers seeking to promote student-centered, context-aware mathematics education.